Soft-combustion synthesis of a new cathode-active material, LiVWO6, for lithium-ion batteries - Prabaharan, S.R.S.; Yong, Tou T.; Fauzi, Ahmad; Michael, M.S. (2001)
Brannerite-LiVWO6, has been synthesized by employing a wet-chemical soft-combustion (low temperature) technique and its battery-active character as candidate cathode material in lithium-containing batteries is reported in the light of electrochemical means. Structural and thermal properties have also been studied by means of classical techniques such as XRD and thermal analysis. The structural features are found to be similar to its analogous counterpart, brannerite-LiVMoO6 previously reported. Quasi-layered type LiVWO6 crystallizes in brannerite structure of AB(2)O(6) type, having a general formula LiM2'O-6 (M ' = transition metal) with lattice parameters a = 9.347 Angstrom, b = 3.670 Angstrom, c = 6.593 Angstrom and beta = 111 degrees 50 '. The thermochemical reactions that occur during the soft-combustion of the precursor mass facilitate the formation of the above compound at 434 degreesC as deduced from TG-DTA scan. The product (LiVWO6) thus prepared (calcined at 700 degreesC) exhibits the submicrometer grains (<1 mum) whose specific surface area is found to be 4.97 m(2)/g as deduced from BET analysis. The redox behavior of the above compound has been examined for LiVWO6/Li+/Li under the wet electrolyte (1 M LiPF6: EC + DMC) environment in the voltage regime 4.0 and 1.5 V using constant current technique at a current density of 0.8 mA/cm(2). It has been found that the test cell containing LiVWO6/Li couple demonstrates excellent charge-discharge behavior in the voltage regime 3.0-1.5 V and the specific capacity of similar to 240 mAh/g has been deduced from the first charge-discharge cycle in the voltage regime similar to4.0-1.5 V. (C) 2001 Elsevier Science B.V. All rights reserved.